Evaluating the impact of solar radiation on pediatric heat balance within enclosed, hot vehicles. Issue 3 (3rd July 2018) - Vanos, Jennifer K.; Middel, Ariane; Poletti, Michelle N.; Selover, Nancy J.
ABSTRACT: Pediatric deaths due to children being left in hot cars remain a significant yet preventable public health concern. The current study aims to demonstrate the influence of vehicle type, time of day, and solar exposure (sun or shade) on the energy balance and core temperature (Tc ) of a hypothetical two-year old boy left in a vehicle on a hot day. Cabin temperatures and relative humidity were collected within six enclosed vehicles under sun or full shade in Tempe, Arizona. These variables and radiation estimates were used to estimate the human energy balance and final Tc across 76 measurement cycles lasting approximately 60minutes. Interior temperatures averaged 39.5°C and 47.6°C in the shade and sun, respectively, at steady-state. Based on the specific heat of a human body, the average Tc after 60 minutes in shaded or sun-exposed vehicles was estimated to reach 38.2±0.29°C and 39.1±0.41°C, respectively, with a significantly higher final Tc in sun-exposed vehicles across all days and in the shaded minivan. Extrapolation to 2 hours is estimated to result in heat injury in the sun. Results demonstrate the influence of radiation on a child's thermal balance in a hot and dry environment. In real-world situations, it is critical to acknowledge variability between children, the starting car environment, and climate (e.g., humid versus dry), and that a child left in any vehicle car can experience potentially lethal core temperatures if forgotten, as shown by vehicular heat stroke statistics. Findings may improve public messaging and reinforce the need for policy action and technological adoption to prevent injury and death.